Perceptions and usage of AI-based applications among plantation students in Malaysian higher education - Abdul Rahman, Noor Zubaidah; Ahmad, Normala; Abd Rashid, Nur Hidayah; Abdul Hakim, Nornazeeha; Abdul Raof, Wan Nur Aisyah; Vaiappuri, Selvakkumar K N (Faculty of Information Management, 2025)
The integration of artificial intelligence (AI) applications in higher education has transformed traditional academic practices offer new opportunities for enhanced learning. However, limited attention has been given to how students in agriculture and plantation-related fields perceive and engaged with AI in their academic activities. This study examines the perceptions, usage patterns and acceptance of AI-based applications among plantation students in MARA University of Technology (Melaka Branch, Jasin Campus). A total of 150 students across diploma, bachelor, and master’s programs participated in the study. Data were collected using a structured questionnaire covering five dimensions: types of AI application used, role of AI in learning, perceived benefit s and limitations, impact on academic tasks, and ethical considerations. Descriptive statistical analyses revealed that AI applications particularly ChatGPT, QuillBot and Copy.ai were frequently used for assignments, paraphrasing, and academic research. Students largely perceived AI as useful, with noted benefits in writing improvement and time efficiency. Nonetheless, concerns about content reliability, overdependence and ethical implications were reported. Approximately half of the respondents expressed willingness to continue using AI applications and recommending them to others. The study concludes that while AI applications are generally well-received, there remains a critical need for guided integration and plantation disciplines to support responsible and effective use in academic and future professional contexts. The findings offer insights for educators, developers, and policymakers in shaping AI-based education strategies.